2002
DOI: 10.1007/bf03030305
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium-induced changes in antioxidant enzyme activities in rice (Oryza sativa L. cv. Dongjin)

Abstract: We studied how the relationship between cadmium (Cd) toxicity and oxidative stress influenced the Brm~th, photo.. synthetic efficiency, lipid peroxidation, and activity of ntimddative enzymes in the roots and leaves of rice (Oryza sat/va L Don~in). Plants were exposed to Cd for 21 d. Both seedling growth and photosynthetic efficiency decreased 8radu-ally with increasin 8 cadmium concentrations. Upid peroxi~ increased slowly in both roots and leaves, causing oxidative stress. However, each tissue type responded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…1). Decrease in growth and in FW or DW was also reported in Cd-treated plants of wheat, barley (Hordeum vulgare L.) and rice (Oryza sativa L.) [2,36,38,43]. Particularly in wheat plants, addition of Cd to the nutrient solution decreased shoot and root weight and length, with a growth inhibition varying between roots and shoots and among genotypes [47].…”
Section: Plant Growth and Dry Weightmentioning
confidence: 74%
See 1 more Smart Citation
“…1). Decrease in growth and in FW or DW was also reported in Cd-treated plants of wheat, barley (Hordeum vulgare L.) and rice (Oryza sativa L.) [2,36,38,43]. Particularly in wheat plants, addition of Cd to the nutrient solution decreased shoot and root weight and length, with a growth inhibition varying between roots and shoots and among genotypes [47].…”
Section: Plant Growth and Dry Weightmentioning
confidence: 74%
“…Both increase and decrease in the activity of many antioxidant enzymes has been observed in Cd-treated plants [2,13,26,33], suggesting that the antioxidant systems, beside being involved in detoxification process, could be sensitive targets of Cd toxicity.…”
Section: Introductionmentioning
confidence: 98%
“…We previously showed that reduction in Fv/Fm ratio (Fig. 1A), was related to oxidative stress [1,32], but which was not related to chilling and drought stresses (Fig. 1B).…”
Section: Discussionmentioning
confidence: 82%
“…In addition to causing accumulation of toxic metals, heavy metal stress can also affect the absorption of essential mineral elements in plants, and different kinds of heavy metals exert different effects on absorption of mineral elements in different plants [11]. This study found that the Cu 2+ treatment not only inhibited the absorption of P, K, Ca, Mg by S. sagittifolia roots to different degrees (Figure 1), but also made P, K and Mg transport to leaves excessively, which eventually caused contents of P, K and Mg in leaves higher than those in the roots, while Ca content in leaves was lower than that in roots (Figure 2).…”
Section: Discussionmentioning
confidence: 99%